THE EFFECTIVE TEACHING GRAMMAR ACTIVITIES WITH NO RESOURCES - Sumihatul Ummah MS, S. (OKARA: Jurnal Bahasa dan Sastra, 2013)
Teaching grammar with no resources to be great challenge for many teachers because it is so difficult to be conducted. But there are many ways can be done by the teacher to teach grammar although resources unavailable. This article would like to explain kinds of effective activities in the teaching grammar with no resources. It can help the teachers who will teach grammar by using no resources. Besides that, it also proposes the procedure and variations of theme. Each activity is completed by level, language context of grammar, and age of the learners.